Co-repression of mismatch repair gene expression by hypoxia in cancer cells: Role of the Myc/Max network - Bindra, Ranjit S.; Glazer, Peter M. (Cancer letters, 2007)
The key microenvironmental stress of hypoxia is associated with a diverse spectrum of alterations in both the expression and activation patterns of numerous DNA repair and stress-response factors. We have shown previously that hypoxia causes decreased expression of the mismatch repair gene, MLH1, leading to increased genetic instability in tumor cells, although the mechanism remained to be determined. Here we elucidate a mechanism by which MLH1 and another mismatch repair (MMR) gene, MSH2, are repressed by hypoxia. This repression occurs via a dynamic shift in occupancy from activating c-Myc/Max to repressive Mad1/Max and Mnt/Max complexes at the proximal promoters of both the MLH1 and MSH2 genes. Repression of the MMR genes was also seen in both hypoxia-inducible factor (HIF) proficient and deficient cells, and so ruling out an essential role for HIFs in MMR gene expression. These data highlight a novel HIF-independent stress-response pathway induced by hypoxia leading to the coordinated repression of MLH1 and MSH2, key genes in the MMR pathway, and they provide further insight into the possible mechanisms of hypoxia-induced genetic instability and consequent tumor progression in cancer cells.